2013
DOI: 10.1038/ncomms3824
|View full text |Cite
|
Sign up to set email alerts
|

RhoB controls coordination of adult angiogenesis and lymphangiogenesis following injury by regulating VEZF1-mediated transcription

Abstract: Mechanisms governing the distinct temporal dynamics that characterize post-natal angiogenesis and lymphangiogenesis elicited by cutaneous wounds and inflammation remain unclear. RhoB, a stress-induced small GTPase, modulates cellular responses to growth factors, genotoxic stress and neoplastic transformation. Here we show, using RhoB null mice, that loss of RhoB decreases pathological angiogenesis in the ischaemic retina and reduces angiogenesis in response to cutaneous wounding, but enhances lymphangiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 51 publications
3
54
0
Order By: Relevance
“…Notably, it was reported that RhoB has a critical role in angiogenesis and controls stromal endothelial cells during breast tumorigenesis. 23,39 Among the transcriptional factors involved in mesenchymal migration, we observed that Slug, one of the most thoroughly investigated EMT regulators in lung cancer, 40 was strongly induced following RhoB loss. In parallel, E-cadherin, epithelial marker of EMT known to be downregulated notably by Slug, showed reduced levels of mRNA and protein.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, it was reported that RhoB has a critical role in angiogenesis and controls stromal endothelial cells during breast tumorigenesis. 23,39 Among the transcriptional factors involved in mesenchymal migration, we observed that Slug, one of the most thoroughly investigated EMT regulators in lung cancer, 40 was strongly induced following RhoB loss. In parallel, E-cadherin, epithelial marker of EMT known to be downregulated notably by Slug, showed reduced levels of mRNA and protein.…”
Section: Discussionmentioning
confidence: 96%
“…These distinct posttranslational modifications affect RhoB localization and function . In contrast to RhoA and RhoC, RhoB is localized not only at the plasma membrane but also in endosomes, multivesicular bodies, and has even been reported in the nucleus . Unlike most small GTPases, which are relatively stable, RhoB has a high rate of turnover at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…5 In contrast to RhoA and RhoC, RhoB is localized not only at the plasma membrane but also in endosomes, multivesicular bodies, and has even been reported in the nucleus. [6][7][8] Unlike most small GTPases, which are relatively stable, RhoB has a high rate of turnover at the protein level. Its synthesis is rapidly upregulated by many stimuli, including cellular stress, growth factors, and cytokines, which ultimately helps RhoB regulate many cellular responses like proliferation, survival, and apoptosis.…”
mentioning
confidence: 99%
“…Also, human clinical samples of ATC with BRAF V600E compared to BRAF WT -ATC tend to recruit blood microvascular endothelial cells in the intratumoral area, suggesting that increased ATC-associated angiogenesis might play a role to supply energy/nutrients and support intravascular invasion and ultimately metastasis. It is widely known that VEGFA and VEGFC are potent angiogenic and lymphangiogenic factors [52], respectively, which regulate blood and lymphatic vessels endothelial cell migration and proliferation through the VEGFR2 (vascular endothelial growth factor receptor 2) intracellular signaling cascade [28]. VEGFA [53] and VEGFC [51] have been reported to be highly expressed in PTC over normal thyroid tissue or benign lesions and correlate with increased angiogenesis and lymphatic vessel density [51; 53; 54; 55].…”
Section: Discussionmentioning
confidence: 99%
“…Human thyroid cancer cells were grown in DMEM high glucose (CellGro, USA) medium supplemented with 10% fetal bovine serum (FBS) (CellGro, USA) and ampicillin/streptomycin. Primary human microvascular endothelial cells (blood vessel endothelial cells (BVECs) and lymphatic vessel endothelial cells (LVECs)) [28] were kindly provided from Dr. Harold F. Dvorak (BIDMC, Harvard Medical School, Boston, USA). BVECs and LVECs were grown in MCDB 131 (Life Technologies, USA) growth medium with additional glutgro (Corning, final concentration 2 mM) and MVGS (microvascular growth supplement) (Life Technologies, USA).…”
Section: Methodsmentioning
confidence: 99%